2019
DOI: 10.1016/j.pmedr.2019.100952
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of physical activity among adults and older adults from Black and Minority Ethnic groups in the UK: A systematic review of qualitative studies

Abstract: Older adults from Black and Minority Ethnic (BME) groups experience a relatively higher burden of physical inactivity compared with their counterparts from non-BME groups. Despite the increasing number of qualitative studies investigating the barriers and facilitators of physical activity among older adults from BME backgrounds in the UK, there is very limited review-level evidence. The aim of this review is to undertake a synthesis of existing qualitative studies, using a meta-ethnographic approach, to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 49 publications
(121 reference statements)
1
42
0
Order By: Relevance
“…Nonetheless, for both walking and running outcome measures, we found that all other ethnic groups combined engaged in less PA than White ethnic groups throughout the observation period. This is in keeping with previous studies generally showing lower rates of PA among ethnic minority groups [ 28 , 29 ]. However, small sample sizes prevented us from exploring these differences using more granular ethnicity groupings.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, for both walking and running outcome measures, we found that all other ethnic groups combined engaged in less PA than White ethnic groups throughout the observation period. This is in keeping with previous studies generally showing lower rates of PA among ethnic minority groups [ 28 , 29 ]. However, small sample sizes prevented us from exploring these differences using more granular ethnicity groupings.…”
Section: Discussionsupporting
confidence: 93%
“…The chemical analysis showed that the characterized essential oil possessed many potentially bioactive substances including thujone (29.02%), 2-bornanone (14.68%), octacosane (14.02%) eucalyptol (5.60%), endoborneol (3.78%), bicyclo (3.1.0) hexan-3-on (3.63%), pentacosane (3.07%), and camphene (2.38%). Some compounds identified in the current oil ( β -thujone, α -thujone, borneol, camphor, and 1.8-cineol) were also identified in closer plant species including Artemisia herba-alba L., Artemisia pontica L. , Artemisia absinthium L. [ 25 27 ]. Thujone as a major element in the studied oil has been largely identified in essential oils of plants that are used for food and/or medicinal purposes [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, Whatman paper disks (6 mm in diameter) impregnated with 10 μ L of essential oils were placed on the surface of Petri dishes before being incubated at 30°C in the darkness. The inhibition diameter, as well as inhibition percentage, was determined after 48 h of incubation for C. albicans and after 7 days for A. niger, A. flavus, and F. oxysporum [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Whereas cultural and genetic distinctions likewise add to these inequalities, it is conceivable that these factors could exert their influence diffusely, and that the detrimental effect of lifestyle aspects could be intermediated across their impact on physical activity and sleep. [ 5 8 12 17 ] Besides, various scholars likewise denote an adverse connotation among insalubrious lifestyle behaviors and reduced cognitive capacity and AA. [ 1 19 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 9 10 11 ] Thus, minority ethnic groups suffer a noticeably higher load of ailment than nonminorities. [ 12 ] Furthermore, it has been indicated that minority ethnic groups comprehend less respecting the health consequences of some conducts, including the reduction of sleep;[ 13 ] then, the tiredness concomitant with scarce sleep is usual, and subsequently, sleep complaints are rarely considered problematic. [ 14 15 16 17 18 ]…”
Section: Introductionmentioning
confidence: 99%